SMART HEALTHCARE MODEL FOR HUMAN MONITORING IN THE COVID-19 ZONE USING IOT TECHNOLOGY APPROACH: A SYSTEMATIC LITERATURE REVIEW - Sakti, Satria Audria; Al Hafid, Aldi Akbar; Mariana, Arni Retno; Afrizal; Khoirunisa, Alfiah (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Today, there are still various obstacles faced by the community in protecting themselves from COVID-19 infection and providing valid health services. The purpose of this paper is to explain how healthcare systems interact with IoT technology to provide warnings to users when they are on COVID-19 zoning and provide information on the implementation of health protocols according to zones. The research method used is the SLR (Systematic Literature Review) method, where the data collection process is carried out by documenting all research articles that match the criteria, search string from 2000 to 2020. The results of the discussion of this paper are how to design a framework for improving health information services as an early prevention effort against the dangers of COVID-19. The conclusion from the healthcare system framework can be used as a reference for building IoT-based applications in self-monitoring of the dangers of COVID-19